The Development Of Students’ Ecological Intellegence Through Journalist Activity In The Learning Of Social Studies - Lasminingrat, Gina (International Journal Pedagogy of Social Studies, 2017)
This research began with the observation which was done in VIII-C class SMPN 19 Bandung, there were lack of student’s awareness in keeping class environment, it looked from scatter waste and the lamp that was left turning on when the class began. From the condition, it needs the effort in order to make the students are able to understand a concept of social science material which can increase the ecological intelligent development. The implementation of journalistic activity becomes the alternative that was chosen to develop students’ ecological intelligent development. Journalistic activity aims to make students aware about living environmental issue in their surroundings. Meanwhile, the method that was used was class action research method (PTK) with the design which was developed byKemmis and Mc Taggart in which each cycle consists of planning, action, observation and implementation of reflection. Based on the result of the research of developing students’ ecological intelligence showed enough in first cycle, in cycle 2 and 3 had increasing and they were in good category. Based on the result of three cycles that had been done, there were enhanced in each category. It shows that through journalistic activity, there is enhanced in students’ ecological intelligence.